Pengujian Tingkat Usability Pada Penggunaan Aplikasi Android PalComTech Online Learning dengan Metode PACMAD - Rendy Almaheri Adhi Pratama; Mahmud; Yarza Aprizal; Syaftriandi; Eko Setiawan (CV. Multi Kreasi Media, 2023)
Blended Learning practiced by the PalComTech Institute of Technology and Business in the teaching and Learning activity system describes a combination of 3 teaching and Learning activity systems face-to-face (offline), online (online), and application support. The PalComTech Online Learning Android application is an application for teaching and Learning activities used by the PalComTech Institute of Technology and Business in supporting the ease of teaching and Learning activities online (online). To support teaching and Learning activities digitally, this application provides Learning modules in the form of video material and pdf material. The application of technological sophistication along with the development of the user-friendly PalComTech Online Learning Android Application will run better in carrying out the teaching and Learning process and training easily and can also create a generation of students who are aware of the use of digital technology. Therefore, this research tested the level of Usability in using the PalComTech Online Learning Android application with the PACMAD (People at the Center of Mobile Application Development) method which consists of factors of Effectiveness, Efficiency, Satisfaction, Learnability, Errors, Memorability, and Cognitive Load.